Endothelial Jagged-1 Is Necessary for Homeostatic and Regenerative Hematopoiesis - Michael G. Poulos; Peipei Guo; Natalie M. Kofler; Sandra Pinho; Michael C. Gutkin; Anastasia Tikhonova; Iannis Aifantis; Paul S. Frenette; Jan Kitajewski; Shahin Rafii; Jason M. Butler (Cell Reports, 2013)
The bone marrow (BM) microenvironment is composed of multiple niche cells that, by producing paracrine factors, maintain and regenerate the hematopoietic stem cell (HSC) pool (Morrison and Spradling, 2008). We have previously demonstrated that endothelial cells support the proper regeneration of the hematopoietic system following myeloablation (Butler et al., 2010; Hooper et al., 2009; Kobayashi et al., 2010). Here, we demonstrate that expression of the angiocrine factor Jagged-1, supplied by the BM vascular niche, regulates homeostatic and regenerative hematopoiesis through a Notch-dependent mechanism. Conditional deletion of Jagged-1 in endothelial cells (Jag1(ECKO) mice) results in a profound decrease in hematopoiesis and premature exhaustion of the adult HSC pool, whereas quantification and functional assays demonstrate that loss of Jagged-1 does not perturb vascular or mesenchymal compartments. Taken together, these data demonstrate that the instructive function of endothelial-specific Jagged-1 is required to support the self-renewal and regenerative capacity of HSCs in the adult BM vascular niche.